Implementasi Model Pembelajaran Numbered Head Together (NHT) dan Group Investigation (GI) Untuk Meningkatkan Motivasi dan Hasil Belajar Siswa Pada Mata Pelajaran Kewirausahaan - Mukhamad Zulianto (JURNAL PENDIDIKAN EKONOMI: Jurnal Ilmiah Ilmu Pendidikan, Ilmu Ekonomi dan Ilmu Sosial, 2016)
The purpose of this research to know (1) the implementation of learning model numbered head & apos; together and group investigation to their students class xi multimedia subjects entrepreneurship, (2) learning model numbered head & apos; together and group investigation can increased the motivation to study, (3) learning model numbered head & apos; together and group investigation can improve learning outcomes students .The research is the kind of research actions has class by adopting both qualitative .The result of this research has been proven able to increase the motivation to study students from the cycle to cycle .In cycle i the highest scores obtained is 92 and a score maximum 96 , with the average value of 95,83 % and included in a category very well and gain points a.In cycle ii the highest scores obtained is 94 and a score maximum 96, with the average value of 97,92 % . And included in a category very well and gain points A. In addition this research show some improvement against learning outcomes of students who seen the result of pre-test before the act with the results of pos-test given during the the end of the act of .The results of the cycle pre-test i show students who had been completed as many as 15 students and the 36,59 % and that have not been solved as many as 26 students (63,41 %) .The results of the cycle post-test i show some improvement learning outcomes with students of work completed in as many as 17 students (41.46 %) and that have not been solved as many as 24 students (58,54 %).The results of the cycle pre-test ii show students had been completed as many as 36 students (87,80 %) and that have not been solved as many as 5 students (12,20 %) .To yield post-test cycle ii also show some improvement learning outcomes and the number of students work completed in as many as 37 students (90,24 %) and that have not been solved as much as 4 students (9.76 %)Key Words : numbered head together,group investigation, Motivation, study of results and entrepreneurship